Uchuk - Danilko, Elena (Russia, 2005)
Every spring after the sowing-time the Chuvash inhabitants of the village of Ultimorovka, in the Bakalinski area of Bashkortostan hold an ancient pagan feast of offerings. Lambs are slaughtered and a special meal is prepared for the crowd of the villagers assembled in the field. People eat the chopped lamb meat and pray to the Supreme God named Tura and to seven other deities of the upper world, asking for good harvest and the well-being of the community.
Poor image
Keywords: Documentary films